The prevalence of midline prostatic cysts and the relationship between cyst size and semen parameters among infertile and fertile men - Lotti, F; Corona, G; Cocci, A; Cipriani, S; Baldi, E; Degl'Innocenti, S; Franco, P N; Gacci, M; Maggi, M (Human reproduction (Oxford), 2018)
When is the investigation and treatment of midline prostatic cysts (MPC) of clinical value in the work-up of males of infertile couples? With a prevalence of 10.2% in infertile men, MPC should be investigated according to a seminal algorithm detecting a MPC volume >0.117 ml, which may impair semen parameters, and could be treated to improve sperm count and achieve natural pregnancy. MPC are frequent and are considered a correctable cause of male infertility. However, they have been poorly investigated in an infertility setting. In addition, no study has investigated clinical and ultrasound (US) characteristics of men with MPC. A cross-sectional analysis was carried out of 693 consecutive subjects consulting for couple infertility from September 2012 to March 2017. As a control group, 103 age-matched healthy, fertile men were studied. Furthermore, a longitudinal evaluation of 11 infertile men undergoing trans-rectal ultrasonically-guided cyst aspiration (TRUCA), semen analyses 1 and 3 months after TRUCA and a follow-up 1 year after TRUCA to assess natural pregnancy were performed. All subjects underwent, in our outpatient clinic, clinical, hormonal, scrotal and transrectal US evaluation and semen analysis within the same day. Of 693 males of infertile couples, 648 (37.1 ± 7.9 years, mean+SD) without genetic abnormalities were studied, along with 103 fertile men (36.6 ± 5.0 years). Eleven infertile men underwent TRUCA and were followed-up as reported above. A MPC was present in 66/648 (10.2%) males of infertile couples and in 6/103 (5.8%) fertile men. MPC occurrence and volume were higher in patients with severe oligo- or azoospermia than in fertile men (all P < 0.05). Infertile men with a MPC showed a lower seminal volume and sperm count and a higher prevalence of azoospermia than the rest of the infertile sample or fertile men, and a higher frequency of US signs suggestive of ejaculatory duct obstruction. MPC volume was negatively associated with total sperm count (r = -0.452, P < 0.0001). In fertile men, the highest MPC volume was 0.117 ml, suggesting it as a biological threshold not compromising semen quality. In infertile men, using receiver operating characteristic curve analyses, a MPC volume >0.117 ml identified subjects with severe oligo- or azoospermia with an overall accuracy of ~75% (both P < 0.005). Eleven men with infertility, semen abnormalities and large MPC (>0.250 ml) underwent TRUCA, which led to sperm count improvement in all patients 1 month after surgery. Three months after TRUCA a lower sperm count and a higher MPC volume than 2 months before were observed (P < 0.005 and P < 0.05, respectively), although improved when compared to baseline. After TRUCA a natural pregnancy occurred in four couples. Finally, we propose an algorithm, based on semen parameters, useful in identifying a MPC in males of infertile couples. Although in line with the sample size of previous studies (n = 7-20), the number of infertile men with MPC evaluated longitudinally after treatment is limited (n = 11). In addition, although a MPC volume >0.117 ml can negatively affect the sperm count, only MPC > 0.250 ml have been treated in this study. First, the algorithm proposed is easy to use and useful for selecting patients who can benefit from a prostate US in the infertility work-up. Second, a MPC volume ≤0.117 ml may not impair semen quality, while a larger volume can lead to severe oligo- or azoospermia and could be treated. Third, TRUCA is effective, and simpler and less invasive than other surgical techniques for MPC treatment. Finally, since the MPC can increase in size and sperm count decrease over time after TRUCA, semen cryopreservation should be considered 1 month after TRUCA. Grants from the Ministry of University and Scientific Research (SIR project to F.L., protocol number: RBSI14LFMQ). No conflicts of interest.